The Companions Redefining Criteria and Reconsidering ‘Adâla Critique From Qur’an and Hadith - Muhammad Babul Ulum (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The theory of ‘adâlah al-ṣaḥâbah which is adobted by mainstream hadith experts should be critized. This inseparable from several facts tha are presented to us. Several facts assumed to support the companions justice. Such as companion’s loyalty, obedience, and readiness to sacriface for the prophet. However, we are also confronted with facts which demonstrate their disobedience to the prophet. Arguments ready to sacrifice to defend the prophet contradict other facts that show their efforts to avoid even fleeing from the battlefield. However, how to explain a contradiction like this is a problem that hadith experts have left to float and gave birth to a never-ending debate. This paper puspose to put an end this circular debate by applaying the concept of ‘adâlat al-râwi to the Companions. Using the historical critical method and content analysis, this paper tries to reexamine the concept of ‘adâlah al-ṣaḥâbah by tracing the origin of the word ṣa-ḥâ-bah in the Qur’an and Hadith. And then redifining the criteria of Companions which has implication to their integrity. The behavior of many of the Companions contradicted the instructions of the Qur’an dan Hadith and contrary to the principles of justice made by hadits expert. The concept of ‘adâlah al-ṣaḥâbah is more fitting to be called a dogma rather than a scientific theory because it is not slack in the face of historical analysis